THE ROLE OF EMPLOYEE ENGAGEMENT VARIABLE: IT'S IMPACT OF THE WORK ENVIRONMENT TOWARDS EMPLOYEE PERFORMANCE (A Case Study at Culinary Tourism Sector in the City of Surabaya) - J.E Sutanto; Hari Minantyo; Moses Soediro (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Study this aims for the impact of working environment on employee performance through employee engagement and scope of study on culinary tourism sector in the city of Surabaya. Design/ methodology/approach - This research method uses quantitative methods, and the population is all businessmen at the culinary sector in the city of Surabaya. The data collection method in this study used the research instrument method which was distributed to 55 respondents. Meanwhile, for data processing using the SmartPLS program. Findings – The results of this study found that there are a significant and positive impact on environment work to performance employee through employee engagement. Practical/implementation - This study confirms that businesses in the culinary sector during this pandemic are still quite promising, both online purchases and visits to culinary locations. Original/value - The results of this study contribute to increasing the amount of literature in the culinary sector, both on a city scale, district, or regional and even national scale in Indonesia.